The hundred-year barn - MacLachlan, Patricia (Katherine Tegen Books, an imprint of HarpercollinsPublishers, 2019)
One hundred years ago, a little boy watched his family and community come together to build a grand red barn. This barn become his refuge and home-a place to play with friends and farm animals alike. As seasons passed, the barn weathered many storms. The boy left and returned a young man, to help on the farm and to care for the barn again. The barn has stood for one hundred years, and it will stand for a hundred more: a symbol of peace, stability, caring and community.